THE ROLE OF NASAL FIBEROSCOPY IN OTORHYNOLARYNGOLOGICAL PRACTICE FOR THE EARLY DETECTION OF UPPER AIRWAY CANCERS - Klaudia Bilińska; Patrycja Jędrzejewska-Rzezak; Monika Czekalska; Natalia Kulicka; Kinga Knutelska; Aleksandra Winsyk; Paulina Gajniak; Maciej Karwat; Tytus Tyralik; Joanna Węgrzecka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Nasopharyngeal fiberoscopy is a modern, minimally invasive diagnostic technique that allows for direct, dynamic, and high-resolution visualization of the upper respiratory tract, including the nasal cavity, nasopharynx, oropharynx, and larynx. By using a thin, flexible fiber-optic endoscope, clinicians are able to assess the mucosal surfaces in great detail, identify potential pathological changes, and collect targeted biopsy specimens in a safe and precise manner. Compared to traditional examination methods such as indirect laryngoscopy or mirror examination, fiberoscopy offers significantly improved diagnostic accuracy, greater patient comfort, and the advantage of being performed in outpatient settings without the need for hospitalization. In the field of otolaryngology, early detection of malignancies of the upper aerodigestive tract—such as laryngeal, nasopharyngeal, nasal, and base-of-tongue cancers—remains one of the most important clinical challenges. Detecting neoplastic changes at an early stage dramatically increases the likelihood of effective treatment, reduces the extent of surgical intervention required, and improves long-term prognosis. Consequently, the development and implementation of accurate, accessible, and non-invasive diagnostic tools such as fiberoscopy are of particular importance—not only in clinical practice but also in population-based screening and prevention strategies targeting high-risk groups. This article provides a comprehensive review of current literature concerning the application of nasal fiberoscopy in the early diagnosis of upper airway cancers. It discusses the clinical advantages and limitations of the method, details of the examination procedure, and its role in the differential diagnosis of non-specific symptoms such as chronic hoarseness, globus sensation, or unilateral otalgia. Special attention is given to the integration of fiberoscopy with advanced imaging techniques (e.g., Narrow Band Imaging, autofluorescence, CT, and MRI), as well as the implementation of artificial intelligence and machine learning in real-time diagnostic support systems. Selected clinical cases and PubMed-sourced studies are presented to illustrate the growing clinical relevance and diagnostic effectiveness of this technique. The article also outlines future directions for the development of fiberoscopy and highlights its potential to become a key pillar in personalized head and neck cancer diagnostics in the 21st century. Materials and Methods: This narrative review was based on a comprehensive search of scientific literature in the PubMed, Web of Science, and Google Scholar databases using the following keywords: nasal fiberoscopy, upper airway cancers, early diagnosis, endoscopic screening, otorhinolaryngology, and laryngological fiberoscopy. The analysis included original research articles, review papers, meta-analyses, case reports, and clinical guidelines from scientific societies that addressed the use of nasal fiberoscopy in the diagnosis of upper airway malignancies. The selected publications provided data on diagnostic effectiveness, screening potential, technical capabilities, and integration with imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI), narrow band imaging (NBI), autofluorescence, and artificial intelligence–assisted analysis. The aim was to synthesize current knowledge regarding the clinical value and evolving role of nasal fiberoscopy in the early detection and evaluation of upper aerodigestive tract cancers within otorhinolaryngological practice. Results: The literature analysis revealed that nasal fiberoscopy demonstrates high diagnostic sensitivity and specificity in detecting both precancerous and cancerous lesions within the upper aerodigestive tract. This technique allows for real-time, dynamic assessment of anatomical structures, as well as the performance of targeted biopsies under direct visualization, which significantly enhances diagnostic accuracy. Compared to static imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI), fiberoscopy offers superior evaluation of mucosal surfaces and phonatory function. Numerous studies have confirmed that the use of fiberoscopy in patients presenting with non-specific symptoms - such as hoarseness, dysphagia, or epistaxis - led to early detection of laryngeal, nasopharyngeal, and base-of-tongue cancers. Furthermore, in high-risk populations, including tobacco users, individuals with occupational exposure to carcinogens, or those with a positive oncological family history, nasal fiberoscopy proved more effective in identifying subclinical lesions than clinical observation alone. Several case reports describe instances where routine fiberoscopic examination enabled the identification of early-stage malignancies in asymptomatic patients, which was critical for initiating radical yet function-preserving treatment. These findings highlight the growing importance of nasal fiberoscopy as both a diagnostic and screening tool in contemporary otorhinolaryngological practice. Conclusions: Nasal fiberoscopy is becoming an increasingly important tool in otorhinolaryngological diagnostics. Its advantages - real-time assessment of mucosal structures, the ability to perform targeted biopsies, wide availability in outpatient settings, and low cost—make it applicable both in differential diagnosis and in screening high-risk populations. The literature clearly indicates that nasal fiberoscopy holds significant value as a first-line diagnostic method for patients with suspected neoplastic changes in the upper aerodigestive tract. Integration with modern imaging technologies and artificial intelligence systems may further enhance its diagnostic effectiveness. However, additional large-scale clinical studies are necessary to validate its efficacy and to develop standardized screening protocols. In light of the rising incidence of head and neck cancers and the increasing emphasis on early detection, nasal fiberoscopy has the potential to play a pivotal role in improving treatment outcomes and overall patient survival.